Mechanisms of exercise intervention in type 2 diabetes: a bibliometric and visualization analysis based on CiteSpace - Jin, Yue; Wan, Kang; Liu, Cheng; Cheng, Wei; Wang, Ru (Frontiers in Endocrinology, 2024)
Objective Type 2 diabetes (T2D) is a common chronic metabolic disease, and its prevalence is increasing globally. Exercise is crucial for T2D management, yet many aspects of its mechanisms remain unclear. This study employs CiteSpace to reveal research hotspots and frontier issues in exercise intervention for T2D. Method A literature review spanning from January 1, 2013 to December 31, 2022, was conducted using the Web of Science Core Collection (WoSCC), with keywords including "exercise," "type 2 diabetes," and "mechanisms." We analyzed network diagrams generated by CiteSpace, which depicted relationships among countries, authors, and keywords. Results This study includes 1,210 English papers from 555 journals, affiliated with 348 institutions across 80 countries/regions. Notably, the United States, China, and the United Kingdom account for nearly half of all publications. The University of Copenhagen leads in publication volume, followed by Harvard Medical School and the University of Colorado. Key authors include Kirwan, John P (Case Western Reserve University), Malin, Steven K (Rutgers University), and Pedersen, Bente Klarlund (University of Copenhagen). Based on co-occurrence analysis of keywords, it is evident that terms such as "disease," "glucagon-like peptide 1," and "cardiovascular risk factor" exhibit high intermediary centrality. Conclusion The analysis highlights ongoing investigations into molecular mechanisms, such as β-cell function enhancement, exerkines, and epigenetic mechanisms. Emerging areas include exercise response heterogeneity, circadian rhythm regulation, transcription factors, neurotrophic factors, and mitochondrial function. Future studies should prioritize understanding interactions between different exercise mechanisms and optimizing exercise prescriptions for T2D. Exercise prescriptions are crucial for effective interventions. Collaboration between countries and institutions is essential to understand the influences of different genetic backgrounds and environmental factors. Currently, a combination of aerobic and resistance training is considered the optimal form of exercise. However, considering time efficiency, high-intensity interval training (HIIT) has gained widespread attention and research due to its ability to achieve similar exercise effects in a shorter duration. Additionally, circadian rhythm regulation may affect the exercise outcomes of diabetic individuals at different times of the day, particularly concerning the specific types, doses, and intensities used for precision intervention in T2D.